2013
DOI: 10.1016/j.bjid.2013.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia trachomatis infection in a sample of northern Brazilian pregnant women: prevalence and prenatal importance

Abstract: The scarcity of data about the effects of chlamydial infection on pregnancy and neonatal outcomes justified this study. Diagnosing and treating chlamydial infection during the third trimester of pregnancy may prevent neonate infection. Therefore, preventive screening should be seen as a priority for early detection of asymptomatic C. trachomatis infection as part of local public health strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 20 publications
2
11
1
3
Order By: Relevance
“…In this study, there was a high number of positive cases (24.39%) of CT in young people aged 15-25 years. This prevalence was higher than that found by Araújo in the city of Goiania, in adolescents and young women, estimated at 19.6% and lower than those found in São Paulo and Santa Catarina (27,28) . Statistical analyses of this trial demonstrated an association of the variable age with the risk of Chlamydia infection (p=0.0060).…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…In this study, there was a high number of positive cases (24.39%) of CT in young people aged 15-25 years. This prevalence was higher than that found by Araújo in the city of Goiania, in adolescents and young women, estimated at 19.6% and lower than those found in São Paulo and Santa Catarina (27,28) . Statistical analyses of this trial demonstrated an association of the variable age with the risk of Chlamydia infection (p=0.0060).…”
Section: Discussioncontrasting
confidence: 68%
“…More recent data have established a prevalence of 56.45% in the endocervical samples from 287 women in São Paulo and Santa Catarina by the PCR method (27) . In another study, conducted in Manaus, with samples from 100 pregnant women by the same method demonstrated positivity of 11% (28) . In this study, there was a high number of positive cases (24.39%) of CT in young people aged 15-25 years.…”
Section: Discussionmentioning
confidence: 87%
“…Foi encontrada uma alta incidência (18%) da infecção urogenital por C. trachomatis em jovens parturientes de uma maternidade de referência de Belém do Pará, o que representa a maior frequência dessa IST em populações de jovens grávidas do Brasil, pois se manteve superior às prevalências identificadas em outras regiões do país, que variaram de 9,4% a 13,9% 7,8,9,10 . A incidência encontrada também é superior a de outros estudos que investigaram a infecção por C. trachomatis em grávidas de diversas regiões no mundo, mostrando prevalências que variaram de 1,1% a 11,1%…”
Section: Discussionunclassified
“…Isso torna subestimada a epidemiologia dessa infecção. Em algumas cidades brasileiras, infecções em parturientes por C. trachomatis apresentam frequências que variam de 9,4% a 13,9% 7,8,9,10 . O objetivo deste estudo foi verificar a incidência da infecção urogenital por C. trachomatis em parturientes de uma maternidade pública de referência em Belém, Estado do Pará, Brasil, descrevendo os indicadores sociocomportamentais e de reprodução possivelmente associados.…”
Section: Introductionunclassified
“…2 Across the world, 2.5, 3.0, 5.6, 6.7, and 11% prevalence of syphilis, gonorrhoea, HIV, herpes, and chlamydia respectively have been reported in pregnant women. [3][4][5][6] T. vaginalis infection is one of the most prevalent sexually transmitted diseases (STDs). 7 The disease spectrum ranges from estimated 10-50% asymptomatic carriers to individuals with profound acute, inflammatory disease.…”
Section: Introductionmentioning
confidence: 99%